Epigenetic and gene expression changes in the adolescent brain: What have we learned from animal models?. (November 2016) - Mychasiuk, Richelle; Metz, Gerlinde A.S.
Highlights: Human adolescence can be reliably modeled in rodents and non-human primates. Extensive epigenetic modification occurs in the brain during adolescence. Animal models permit the investigation of normal adolescent epigenetic programing. Pre- and post-natal experiences of the individual modify developmental trajectories. Abstract: Adolescence is defined as the gradual period of transition between childhood and adulthood that is characterized by significant brain maturation, growth spurts, sexual maturation, and heightened social interaction. Although originally believed to be a uniquely human aspect of development, rodent and non-human primates demonstrate maturational patterns that distinctly support an adolescent stage. As epigenetic processes are essential for development and differentiation, but also transpire in mature cells in response to environmental influences, they are an important aspect of adolescent brain maturation. The purpose of this review article was to examine epigenetic programming in animal models of brain maturation during adolescence. The discussion focuses on animal models to examine three main concepts; epigenetic processes involved in normal adolescent brain maturation, the influence of fetal programming on adolescent brain development and the epigenome, and finally, postnatal experiences such as exercise and drugs that modify epigenetic processes important for adolescent brain maturation. This corollary emphasizes the utility of animal models to further our understanding of complex processes such as epigenetic regulation and brain development.